Therapeutic lumbar puncture and lumbar drainage: which is more effective for the management of intracranial hypertension in HIV patients with cryptococcal meningitis? Results of a prospective non-randomized interventional study in China. (4th May 2022) - Xu, Xiao-lei; Zhao, Ting; Huang, Yan-qun; Lu, Yan-qiu; He, Xue-jiao; Wu, Yu-shan; Zhang, Wei; Yu, Jian-hua; Yang, Tong-tong; Xu, Li-jun; Lan, Ke; Zhang, De-fa; et al.
Abstract: Objective: This study aimed to evaluate the effectiveness of therapeutic lumbar drainage (LD) compared to therapeutic lumbar puncture (LP) for the management of intracranial hypertension (ICH) among HIV-positive patients with cryptococcal meningitis (CM). Methods: The study was a multicenter prospective non-randomized interventional clinical trial. One hundred and sixteen HIV-associated CM patients were identified who presented with ICH (≥250 mmH2 O). The LP group comprised 76 cases, while the LD group consisted of 40 cases. We compared mortality, intracranial pressure (ICP) normalization rate, and clinical symptom remission at 10 weeks, between the two groups. Results: The cumulative mortality at week 10 was 22.4% in the LP group and 20% in the LD group ( p  = .927), without any significant difference in mortality between the two groups. Improvement after treatment at 2-weeks, ICP normalization, and headache reversal event occurrence in the two groups showed no significant difference ( p  > .05). The incidence of CSF Cryptococcus clearance at two weeks in the LD group was significantly higher than in the LP group ( p  < .05). The frequency of invasive lumbar therapeutic procedures in the LP group during the first week was higher than that of the LD group ( p  < .05). Localized infection at the puncture site occurred more frequently in the LD group than in the LP group ( p  < .05). Conclusion: For HIV-positive CM patients with an elevated ICP, LD and LP are comparably effective and safe options to normalize ICP. LP increases the frequency of invasive lumbar therapeutic procedures but does not incur more risk of infection events at the puncture site, while LD may accelerate CSF Cryptococcus clearance but may induce more frequent localized infection. Trial registration: This study was registered as one of 12 trials under a general project at the Chinese Clinical Trial Registry (ChiCTR1900021195).